2015
DOI: 10.1177/2040206615589035
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the anti-enterovirus activity of a series of pleconaril/pirodavir-like compounds

Abstract: Background: The Enterovirus genus of the Picornaviridae is represented by several viral pathogens that are associated with human disease, namely Poliovirus 1, Enterovirus 71 and Rhinoviruses. Enterovirus 71 has been associated with encephalitis, while Rhinoviruses are a major cause of asthma exacerbations and chronic obstructive pulmonary disease. Based on the structure of both pleconaril and pirodavir, we previously synthesized some original compounds as potential inhibitors of Rhinovirus replication. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…[43] However, clinical experience with these is very limited, and none had significant antiviral activity against the strains of EV-D68 that circulated in 2014. [44] Other novel specific inhibitors of enterovirus have been identified.…”
Section: Treatment Of Enteroviruses: Recent Progressmentioning
confidence: 99%
“…[43] However, clinical experience with these is very limited, and none had significant antiviral activity against the strains of EV-D68 that circulated in 2014. [44] Other novel specific inhibitors of enterovirus have been identified.…”
Section: Treatment Of Enteroviruses: Recent Progressmentioning
confidence: 99%
“…Results showed that RA inhibited EV71 infection more efficiently when it was present continuously during virus–cell adsorption than if added before adsorption (Fig. 2a and b), as is the case for pleconaril/pirodavir-like anti-EV71 compounds [29]. The highest inhibitory activity of RA occurred during viral infection, at the early stage of EV71 infection (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…Despite promising in vitro results, the two well-known pocket binders pleconaril and vapendavir ( Figure 2 ), have failed the clinical trials due to their low efficacy and several side effects. Nevertheless, their discovery raised interest in the search for analogues [ 14 , 15 ].…”
Section: Direct-acting Antiviralsmentioning
confidence: 99%
“…Bernard et al studied CV-B3 and echovirus inhibitors and found that compound 6501 ( Figure 3 ) was active with an EC 50 of 11 µM [ 14 ].…”
Section: Direct-acting Antiviralsmentioning
confidence: 99%